Energy and cost analysis of photo voltaic trombe wall system in tropical climate - Irshad, K. (Elsevier Ltd, 2014)
The present study examines the performance of a single zone building integrated with PV Trombe wall(PV-TW) in term of potential cost savings, energy consumption and emission reduction by varying PV Glazing types (i.e. PV Single Glazing, PV Double glazing, PV Double glazing filled with gas (Argon)). TRNSYS software is used for simulation in which inputs like climatic conditions, building construction details, thermal properties of materials, detail of PV-TW and orientation of the building were inserted. By comparing the results of all three types of glazing The annual cost saving due to application of single glass PV-TW was RM 485.35; Double glass PV-TW was RM 819.15 while Double glass filled with argon PV-TW was RM 1016.24.While CO2 emission reduction is maximum in double glass filled with argon PV-TW 2588 kg/yr followed by double and single glass PV-TW as 1768 and 1277 kg/yr respectively.The analysis suggests that the application of double glass filled with argon PV-TW in Malaysia climatic condition would be economically viable from the point of view of saving in cooling energy cost and CO2 Emission . Â© 2014 Elsevier Ltd.